Phytochemical characterization of Typha domingensis and the assessment of therapeutic potential using in vitro and in vivo biological activities and in silico studies - Dilshad, Rizwana; Khan, Kashif-ur-Rehman; Ahmad, Saeed; Shaik Mohammad, Asif Ansari; Sherif, Asmaa E.; Rao, Huma; Ahmad, Maqsood; Ghalloo, Bilal Ahmad; Begum, M. Yasmin (Frontiers in Chemistry, 2023)
Typha domingensis, a medicinal plant with significant traditional importance for curing various human diseases, has potentially bioactive compounds but was less explored previously. Therefore, this study aims to investigate the therapeutic potential of T. domingensis by evaluating the phytochemical profile through HPLC techniques and its biological activities (In-vitro, In-vivo) from methanolic extract derived from the entire plant (TDME). The Secondary metabolites profile of TDME regulated by RP-UHPLC-MS revealed some bioactive compounds by -ve mode and +ve modes of ionization. The HPLC quantification study showed the precise quantity of polyphenols (pcoumaric acid; 207.47, gallic acid; 96.25, and kaempferol; 95.78 µg/g extract). The enzyme inhibition assays revealed IC 50 of TDME as 44.75 ± 0.51, 52.71 ± 0.01, and 67.19 ± 0.68 µgmL -1 , which were significant compared to their respective standards (indomethacin; 18.03 ± 0.12, quercetin; 4.11 ± 0.01, and thiourea; 8.97 ± 0.11) for lipoxygenase, α-glucosidase, and urease respectively. Safety was assessed by in vitro hemolysis (4.25 ± 0.16% compared to triton × 100; 93.51 ± 0.36%), which was further confirmed (up to 10 g/kg) by in vivo model of rats. TDME demonstrated significant (p<0.05) potential in analgesic activity by hot plate and tail immersion tests, and anti-inflammatory activity by carrageenan-induced hind paw edema model. Pain latency2 This is a provisional file, not the final typeset article decreased significantly and the anti-inflammatory effect increased in a dose-dependent way. Additionally, in silico molecular docking revealed that the1,3,4,5-tetracaffeoylquinic acid and formononetin 7-O-glucoside-6''-O-malonate possibly contributing to enzyme inhibitory activities due to their higher binding affinities than standard inhibitors. In-silico ADMET study also predicted the pharmacokinetics and safety of the chosen compounds identified from TDME. To sum up, it was shown that TDME contains bioactive chemicals and has strong biological activities. The current investigations on T. domingensis could be extended to explore its potential applications in nutraceutical industries and encourage the isolation of novel molecules with anti-inflammatory and analgesic effects.